Exceptional Field-like Spin-Orbit Torques in Pd/Co Heterostructures Enabled by Interfacial Spin-Orbit Coupling - Jang, Seung-Hun; Park, Gyuyoung; Yun, Deok Hyun; Koo, Hyun Cheol; Kim, Sang-Koog; Lee, Oukjae (AMER CHEMICAL SOC, 2025)
Spin-orbit torque (SOT) has gained significant attention as a fundamental mechanism for next-generation spintronic devices. While most prior studies have focused on the damping-like torque (DLT) arising from bulk-driven spin Hall effects, the field-like torque (FLT) is often deemed to be negligible. Here, we experimentally demonstrate an exceptionally large FLT in a Pd/Co bilayer system, up to 20-40 times higher than that in Pd/CoFe or Pd/Py bilayers and even exceeding the corresponding DLT. A careful analysis of effective magnetic damping, spin-mixing conductance, and surface anisotropy indicates that strong interfacial spin-orbit coupling (ISOC) and magnetic proximity effects at the Pd/Co interface are key to enhancing both FLT and DLT, with the former showing especially remarkable enhancement. Moreover, micromagnetic simulations confirm that this large FLT enables rapid magnetization switching, offering significant advantages for high-speed, low-power magnetic memory applications. These findings highlight the critical role of interfacial engineering in achieving efficient SOT functionalities, paving the way for advanced spintronic devices leveraging robust interface-driven effects.